Improving the production and utilization of sorghum and pearl millet as livestock feed: methodological problems and possible solutions - Blümmel, Michael; Zerbini, E.; Reddy, B.V.S.; Hash, C.T.; Bidinger, F.R.; Ravi, D. (Elsevier, 2003)
The overall objective of this work was the identification of simple, yet accurate, assessments of fodder quality of sorghum and pearl millet stover in crop improvement programs. Stover from 12 genotypes of sorghum and six genotypes of pearl millet grown under high and low fertilizer application was investigated for nitrogen, cell wall constituents, sugar, plant height, stem diameter, leaf number per plant and extent and rate of in vitro gas production of whole stover and of stover cell walls. Organic matter digestibility, organic matter intake, digestible organic matter intake (DOMI) and cell wall digestibility were measured in bulls. Significant genotypic variation was found for chemical, morphological and in vitro fermentation characteristics of stover but their relationship with digestibility and intake measurements was generally poor. While no single chemical, morphological or in vitro measurement described stover quality adequately, some combinations of these measurements resulted in good overall relationships with stover quality measurements. Across sorghum and pearl millet, 71% (P<0.0001) of the variation in stover cell wall digestibility in bulls was accounted by the lag phase of in vitro gas production from cell wall preparations and by acid detergent lignin and acid detergent fiber content of stover. In pearl millet, 98% (P<0.0001) of the variation in DOMI in bulls was accounted for nitrogen, lag phase and maximum rate of gas production and neutral detergent fiber content. The paper further discusses relationships between indirect animal performance measurements such as digestibility and voluntary feed intake (VFI) and animal productivity, e.g. live weight gain. VFI is shown to be a more crucial quality assessment in crop residues than digestibility and the relationship between both measurements was shown to be poor. It is argued that crop improvement programs should validate laboratory techniques as well as indirect animal performance measurements with direct animal performance measurements such as milk or meat production before deciding on laboratory selection criteria.